PERANCANGAN APLIKASI PHOTO SHARING DAILY INSPIRATION SOCIAL MEDIA BERBASIS WEB (Studi Kasus : Briancleo.com) - Brian Cleopatra Humdiana, S.Kom., MM., M.Kom (Institut Bisnis dan Informatika Kwik Kian Gie, 2016)
In principle this website becomes a place to upload photos of each user equipped with other features, so that one user with another user can see each other photos that they upload. Completed with the slideshow feature will make it easier for the user because the slideshow is to display the inspirational photos automatically. Analysis of the running system used is with qualitative research and descriptive research where the method of analysis, researchers analyze the needs of users. At the design stage Researchers design the stages used in website creation. The achieved results is the formation of a website photo sharing daily inspiration. Website photo sharing daily inspiration is a means to exchange photos among users. The conclusion of this research is when using website photo sharing daily inspiration this can give ease and comfort for every user. So this website can be useful for anyone who uses it.Â Keyword : Photo Sharing, Daily Inspiration Sosial Media, web.